Mps1 Mediated Phosphorylation of Hsp90 Confers Renal Cell Carcinoma Sensitivity and Selectivity to Hsp90 Inhibitors - Woodford, Mark R. (Cell Rep, 2016)
The molecular chaperone Hsp90 protects deregulated signaling proteins that are vital for tumor growth and survival. Tumors generally display sensitivity and selectivity toward Hsp90 inhibitors; however, the molecular mechanism underlying this phenotype remains undefined. We report that the mitotic checkpoint kinase Mps1 phosphorylates a conserved threonine residue in the amino-domain of Hsp90. This, in turn, regulates chaperone function by reducing Hsp90 ATPase activity while fostering Hsp90 association with kinase clients, including Mps1. Phosphorylation of Hsp90 is also essential for the mitotic checkpoint because it confers Mps1 stability and activity. We identified Cdc14 as the phosphatase that dephosphorylates Hsp90 and disrupts its interaction with Mps1. This causes Mps1 degradation, thus providing a mechanism for its inactivation. Finally, Hsp90 phosphorylation sensitizes cells to its inhibitors, and elevated Mps1 levels confer renal cell carcinoma selectivity to Hsp90 drugs. Mps1 expression level can potentially serve as a predictive indicator of tumor response to Hsp90 inhibitors.